Disconnecting from global finance : de-risking - the impact of AML/CFT regulations in Commonwealth developing countries (The Commonwealth LondonGB, 2016)
Draws together work undertaken by the Commonwealth Secretariat on de-risking in the Commonwealth. Seeks to complement and enhance previous research undertaken by international organisations, such as the Financial Stability Board, the Financial Action Task Force and the World Bank, and by research institutes, such as the Center for Global Development. Aims to improve understanding on the issues surrounding de-risking and, to identify a number of practical solutions to the de-banking of legitimate banks, businesses and individuals.
Keywords: INTERNATIONAL BANKING